Muslims’ encounter with the English language: a study of Ismail Raji al Faruqi’s concept of Islamic English - Hasan, Md. Mahmudul (2011)
In the mid-twentieth century, there were about half a million English words which doubled at the turn of the century. This spectacular vocabulary growth has taken place because of massive, continuous borrowings from different languages. However, concerning the inclusion of Arabic Islamic terms in English, this culture of borrowing has been less enthusiastic, for which Ismail Raji al Faruqi (1921-1986) partly blames the past “spiritual and intellectual tyranny of the Church.” Conversely, although several hundred million Muslims use English as their first or second language and more books on Islam are now published in it than in any other language, the way Muslim names and Islamic terms are transliterated and translated into English shows loyalty to the language and not to meaning. Based on this theoretical premise, I will examine al Faruqi’s concept of ‘Islamic English’ in the light of the twin strategies of ‘abrogation’ and ‘appropriation’ and will explicate how Muslim names and Islamic terms can enter the English language without semantic distortion, and can continue enriching the language that has gone truly global.